Don't want you like a best friend : a novel - Alban, Emma R. (Alban, Emma R. Mischief and matchmaking, 2024)
"A...queer Victorian romance in which two debutantes distract themselves from having to seek husbands by setting up their widowed parents, and instead find their perfect match in each other"--